2003
DOI: 10.1177/154405910308200312
|View full text |Cite
|
Sign up to set email alerts
|

Human Masticatory Muscle Forces during Static Biting

Abstract: Muscle forces determine joint loads, but the objectives governing the mix of muscle forces involved are unknown. This study tested the hypothesis that masticatory muscle forces exerted during static biting are consistent with objectives of minimization of joint loads (MJL) or muscle effort (MME). To do this, we compared numerical model predictions with data measured from six subjects. Biting tasks which produced moments on molar and incisor teeth were modeled based on MJL or MME. The slope of predicted vs. ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 20 publications
3
56
0
2
Order By: Relevance
“…Results from Nickel et al (2003) support current findings with the fact that the criterion minimization of muscle effort gives reasonable correlations with experimental results. The present model can be used to analyze shoulder joint forces throughout propulsion, and may be useful as a prescriptive tool in determining ideal axle placement for those either newly injured, or may be used in an intervention for those seeking relief from shoulder pain.…”
Section: The Modelsupporting
confidence: 90%
“…Results from Nickel et al (2003) support current findings with the fact that the criterion minimization of muscle effort gives reasonable correlations with experimental results. The present model can be used to analyze shoulder joint forces throughout propulsion, and may be useful as a prescriptive tool in determining ideal axle placement for those either newly injured, or may be used in an intervention for those seeking relief from shoulder pain.…”
Section: The Modelsupporting
confidence: 90%
“…So it seems that only using the min/max criterion might not be valid in all cases. However, when studying the results of Nickel et al (2003) one can observe that the criterion minimization of muscle effort gives reasonable correlations with experimental results for all cases. Only for incisor biting the criterion minimization of joint loads gave a somewhat better result in some subjects, while at the same time this criterion gave bad results for the other subjects.…”
Section: The Modelsupporting
confidence: 52%
“…The muscle recruitment was predicted using a min/max criterion, which is the same as minimization of muscle effort. Nickel et al (2003) and Iwasaki et al (2003) found that predicted muscle outputs during unilateral biting were consistent with minimization of joint loads or minimization of muscle effort, or both, depending on the subject. So it seems that only using the min/max criterion might not be valid in all cases.…”
Section: The Modelmentioning
confidence: 91%
“…Another prime limitation with regard to the development of accurate FEM models pertains to taking the interindividual differences into account. In this regard, models developed via in vivo measurements in single humans (Hirose et al, 2006;Koolstra, 2003;Koolstra andvan Eijden, 1997a, 1997b) can be validated for accuracy with data obtained from validated models of inter-individual differences in joint loads Nickel and Iwasaki, 2004;Nickel et al, 2003).…”
Section: A Perspective On 3-d Computational Reconstruction Of the Hummentioning
confidence: 99%